Lithium disilicate crown, zirconia hybrid abutment and platform switching to improve the esthetics in anterior region: A case report - Adolfi, Dario [UNESP]; Tribst, João Paulo Mendes [UNESP]; Adolfi, Maurício; Dal Piva, Amanda Maria de Oliveira [UNESP]; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP]; Bottino, Marco Antonio [UNESP] (Taylor & Francis, 2020)
The hybrid abutment emerged as an alternative to maintain a stable and favorable volume of peri-implant tissue; it is composed of a mesostructure in ceramic and a metallic connection, which can be machined according to the peri-implant emergence profile. This case report presented the clinical steps for a dental implant with immediate provisional restoration, followed by the installation of implant-supported all-ceramic crowns with zirconia abutment and platform switching. A 40-year-old male patient was rehabilitated with an implant-supported ceramic crown in the region of element 11 and a ceramic veneer was cemented on the upper right central incisor. To do so, an atraumatic extraction of the upper left central incisor was performed followed by implant placement and immediate loading. In this case, a zirconia hybrid abutment was used with a metallic link in the cervical region with a concave platform switching base. This association of clinical steps enabled improving the aesthetics in the anterior dental region.
Keywords: Adhesive; Dental implants; Esthetic; Soft tissue